Functional outcomes of arthroscopic transosseous rotator cuff repair using a 2-mm tape suture in a 137-patient cohort - Beauchamp, Jean-Étienne (JSES international, 2021)
© 2021 Published by Elsevier Inc. on behalf of American Shoulder and Elbow Surgeons.